Diet composition of two common mole‐rat populations in arid and mesic environments in South Africa as determined by stable isotope analysis. (12th September 2016) - Robb, G. N.; Harrison, A.; Woodborne, S.; Bennett, N. C.
Abstract: The common mole‐rat Cryptomys hottentotus hottentotus is a small, subterranean mammal found in southern Africa which lives in social colonies. They harvest their food resources from below ground by extending their burrow systems, and are considered to be geophyte (bulbs, tubers and corms) specialists. This study examines differences in diet composition between populations of common mole‐rats inhabiting arid and mesic areas, by using stable isotope analysis to investigate dietary niches and estimate their reliance on different food resources. We sampled three tissue types, blood, claws and fur, to provide dietary information over different time periods (weeks to months). In addition, we collected and analysed potential food sources adjacent to burrows. We found that the diets of common mole‐rats in both the arid and mesic areas were composed predominantly of geophytes. However, mole‐rats in the arid area had a wider dietary niche, with a larger range in both δ 15 N and δ 13 C values which was consistent across all tissue types. Mole‐rats in arid areas also showed a greater reliance on alternative food sources, such as clover and grass, in addition to geophytes comprising 59–69% of the diet in the arid area, compared to 91–92% of the diet in the mesic area. We suggest that the lower geophyte density in the arid area led to a greater reliance on other food resources by the mole‐rats, and that this decrease in diet specialization could be an adaptation to surviving in more arid areas. We demonstrate that stable isotope analyses can be used to examine interpopulation dietary differences within the same species living in contrasting environments. Abstract : This study examines differences in diet composition between populations of common mole‐rats inhabiting arid and mesic areas in South Africa, using stable isotope analysis to investigate dietary niches and estimate their reliance on different food resources. We found that the diets of common mole‐rats in both the arid and mesic areas were composed predominantly of geophytes. However, mole‐rats in the arid area had a wider dietary niche, with a greater reliance on grass and clover.